Gidget’s gadget’s / Muhammad Firas Kaisar Mahardika Mohd Zaidi ...[et al.] - Mohamad Azlan, Airin Shazwin; Roslan, Muhammad Iqmal Haqeem; Ruslan, Nayli Fatini; Hasni, Nur Firdina; Mohd Zaidi, Muhammad Firas Kaisar Mahardika (2023)
Gidget's Gadget's enterprise provides a variety of attractive casings and customers can also request custom mobile phone casings according to their preferences. Our target and strategy is to meet the needs and want to satisfy customers with high quality goods and low prices that we provide. Our store's target segmentation is in all age range especially teenagers. We will always look forward to ensure that customers are always satisfied with our services. Our service will also inspire and aspire to all gadget enthusiasts to give them a taste of something new and interesting. We will also play many roles that cover various aspects to and constantly learn to improve and become a complete company in the market. Furthermore, now almost 90% of Malaysians have used smartphones. This should be able to give a good response from customers to use our services despite the competition from various existing gadget shops, but Gidget's Gadget's will always be eager to provide the best service. Our business is run by five main workers who are general manager, administration manager, marketing manager, operation manager and financial manager. All of us play an important role and always work together to ensure our business is successful. From our point of view, with the location of the store located in a strategic urban area and having many places of learning institutions and shopping places such as malls, so we can get many customers according to our target which is teenagers. We believe, we can achieve the goal by being in that strategic location. We are confident that the experience and courses followed by these main workers can help develop this business much better. The services provided by us such as making online deliveries can also attract the attention of customers because they do not have to bother coming to our store. Finally, we hope that Gidget's Gadget's can grow well in the first location that we will establish. We also strongly believe that this business can develop well from year to year with the demand in the current market.